La Perception visuelle et le regard dans "Le Rouge et le Noir" - Daniélou, Catherine F. (Nineteenth century French studies, 1991)
Staring and glancing suggest an initiation in Le Rouge et le Noir by Stendhal. Eyes are first revealing of personality and Julien is unaware of their expressive power. Yet, as he dec{des to become a "master hero" and to exercise power over others, Julien comes to understand the need to control how to cast his looks. Especially In the second part of the novel, learning about the asceticism of staring plays a role in the growth of Julien's self-knowledge.